Novel Technology and Whole-Process Management in Prefabricated Building Conference Proceedings of The 5th International Prefabricated Building Seminar on Frontier Technology and Talent Training - Xiang, Ping.; Zuo, Liangdong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book discusses the challenges, methodologies, applications in construction, technology and whole-process management of prefabricated buildings. It is a valuable resource for building engineers looking to understand the effective use of technology, construction methods, and management systems. The contributions in this book highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaboration, ultimately advancing the industrialization of buildings and information technology.
Novel construction technologies and materials applied in prefabricated building -- Whole-process management in prefabricated building -- Smart architecture for prefabricated building.
Keywords: Buildings -- Design and construction; Computer-aided engineering; Building Construction and Design; Computer-Aided Engineering (CAD, CAE) and Design